The Use Mobile Learning Game on Students' Self-Regulated Learning in Vocational High School - Triana Rejekiningsih; Sri Sumaryati; Alla’ Junia Nurdin (Journal of International Conference Proceedings, 2022)
Facilitating self-regulated learning for students has become a concern in the current covid pandemic. The digital platform is a learning solution that educational institutions currently use. This paper focuses on using mobile-based games for students' self-regulated learning. The application has been tested on media experts, materials, and media trials for students. An effectiveness test was carried out to determine the effect of games on students' self-regulated abilities. The findings showed that mobile-based games positively affected students' self-regulated learning. The analysis found a significant difference between the students' pretest and posttest scores. This finding also shows that mobile games can improve students' self-regulated learning.Keywords: Mobile learning game, Self-regulated learning, Vocational high school.